PENGARUH PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 1 X KOTO SINGKARAK - Dillawati, Siti Utami (Jurnal Edukasi dan Penelitian Matematika, 2023)
Whether or not the learning objectives of mathematics are achieved can be determined from the outcomes of learning by students. Outcomes of learning are the results shown by students after participating in the process of learning. However, it is still found that the low outcomes of learning by students at SMP Negeri 1 X Koto Singkarak. The research purpose was to describe the outcomes of learning by students in mathematics who used interactive media for learning better than the outcomes of learning by students in mathematics who used learning in conventional. This study uses a type of quasi-experimental research with a non-equivalent post-test only with design of control group. The technique for sampling used technique by purposive sampling with the selected classes being class VIII A and VIII C. The research instrument used was a outcome of learning test in consist of questions in description. The data in research were analyzed using the t test. Through the analysis of data conducted with the t test, obtained a P-value of 0.002 or reject  because it is less than the real level α = 0.05. We got conclussion that the outcomes of learning by students in mathematics who use interactive media for learning are better than the outcomes of learning by students in mathematics who use learning in conventional. Keywords–Learning Outcomes, Interactive Learning Media, Linear Equations.